Empat Pola Pikir Matematika sebagai Teknik Penciptaan Cerita Pendek - Pramulia, Pana; Yustitia, Via (Universitas Mathla'ul Anwar Banten, 2023)
Literary works are written based on the author's experience. The author tries to reflect and analyze the events he experienced into his work. Such a process can be said to be an imaginative process. Besides imagination, writers also need special techniques so that the work presented is well and interesting. One technique that can be used is four mathematical thinking patterns. The four mathematical mindsets include a square mindset, cross mindset, similarity mindset, and difference mindset. This technique functions for regional awareness, conflict building, resolution building, and diction selection. This technique is used by PGSD Study Program students to create short stories. The method in this article uses a qualitative research design with exploratory research types to understand the text and context. Data analysis was carried out by comparing short stories with four mathematical thinking techniques. The results of the research show that PGSD Study Program students understand the rules of short story writing, and can implement the four mathematical thinking techniques for creating short stories.